Remarks on genus Microtachycines Gorochov, 1992 (Orthoptera: haphidophoridae: Aemodogryllinae) from China - Qin, Yan-Yan; Liu, Xian-Wei; Li, Kai (Zootaxa, 2020)
In this work, one new species Microtachycines trispinosus Qin et Li sp. nov. from Sanqingshan of Jiangxi province is described and illustrated with photographs. It is mentioned that Microtachycines fallax Qin, Liu, & Li, 2017 should be regarded as the junior synonym of Microtachycines elongatus Qin, Liu & Li, 2017. All examined specimens are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences (SEM, CAS).